Membrane electrode and proton exchange membrane fuel cell
By introducing a hydrophilic microporous layer and a hydrophobic microporous layer into the anode gas diffusion layer of the membrane electrode, the problem of poor water discharge in the existing membrane electrode is solved, timely water discharge and uniform gas distribution are achieved, and the performance and life of the fuel cell are improved.
Patent Information
- Application Number
- CN202311117947.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-02-28
AI Technical Summary
The gas diffusion layer of the existing membrane electrode cannot effectively discharge moisture on the anode side, resulting in problems such as hydrogen starvation, uneven gas distribution and flooding on the anode side, affecting the performance and life of the fuel cell.
The hydrophilic microporous layer is introduced into the anode gas diffusion layer of the membrane electrode. The hydrophilic microporous layer is close to the anode catalytic layer, and the water vapor generated by the anode catalytic layer is absorbed and transferred through the hydrophilic microporous layer, and then discharged through the hydrophobic microporous layer, thereby achieving timely discharge of water and uniform distribution of gas.
It effectively avoids the flooding and hydrogen starvation on the anode side, improves the gas distribution, improves the life of the membrane electrode and the overall performance of the fuel cell.
Smart Images

Figure CN119542433A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cells, and in particular to a membrane electrode and a proton exchange membrane fuel cell. Background Art
[0002] At present, the gas diffusion layer in the membrane electrode generally mixes conductive carbon black and a hydrophobic agent evenly, and then coats it on the surface of a hydrophobically treated support layer (such as carbon paper, carbon cloth or carbon felt), and then undergoes high-temperature baking to obtain a coating with a certain pore size distribution and a certain hydrophobicity.
[0003] The existing gas diffusion layer only considers the requirements of high-density drainage of membrane electrodes or water retention under low humidity, and rarely involves the uniform distribution of water vapor on the anode side and avoiding anode flooding. When there is local water blockage in the anode flow channel of the fuel cell membrane electrode, the water cannot be completely discharged due to the small volume of hydrogen molecules, and hydrogen starvation may occur locally; the state of water at the interface between the gas diffusion layer and the catalyst layer inside the membrane electrode is in the form of scattered points, which will lead to uneven distribution of gas, and the anode side is also faced with local flooding, and even reverse polarity, leading to carbon corrosion.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] One of the purposes of the present invention is to provide a membrane electrode to alleviate the technical problem of membrane electrode performance degradation caused by the inability to discharge water in the gas diffusion layer in time in the prior art.
[0006] A second object of the present invention is to provide a proton exchange membrane fuel cell.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0008] The first aspect of the present invention provides a membrane electrode, comprising an anode gas diffusion layer, an anode catalyst layer, a proton exchange membrane, a cathode catalyst layer and a cathode gas diffusion layer stacked in sequence;
[0009] The anode gas diffusion layer includes a hydrophilic microporous layer.
[0010] Further, the anode gas diffusion layer comprises a hydrophilic microporous layer, a first hydrophobic microporous layer and a first substrate layer which are stacked in sequence;
[0011] The cathode gas diffusion layer includes a second hydrophobic microporous layer and a second base layer which are stacked in sequence.
[0012] Furthermore, the first substrate layer is arranged on a side away from the anode catalyst layer, and the hydrophilic microporous layer is arranged on a side close to the anode catalyst layer.
[0013] Furthermore, the second substrate layer is arranged on a side away from the cathode catalyst layer, and the second hydrophobic microporous layer is arranged on a side close to the cathode catalyst layer.
[0014] Furthermore, the thickness of the hydrophilic microporous layer is 1 μm-10 μm.
[0015] Preferably, the material of the hydrophilic microporous layer includes 3wt.%-30wt.% of hydrophilic material and the remainder of the first conductive solid material.
[0016] Preferably, the first hydrophobic microporous layer and the second hydrophobic microporous layer are both made of a hydrophobic material and a second conductive solid material.
[0017] Furthermore, the first conductive solid material and the second conductive solid material independently include at least one of carbon powder, carbon fiber, metal powder, conductive polymer material and polymer material with a conductive material coated on the outer layer.
[0018] Preferably, the first conductive solid material is carbon fiber.
[0019] Preferably, the aspect ratio of the carbon fiber is 10-500.
[0020] Furthermore, the first substrate layer and the second substrate layer independently include carbon paper, carbon cloth, carbon felt or non-woven fabric.
[0021] Furthermore, the water contact angles of the first hydrophobic microporous layer and the second hydrophobic microporous layer are independently 120°-150°.
[0022] Preferably, the surface density of the (first substrate layer + first hydrophobic microporous layer) and the (second substrate layer + second hydrophobic microporous layer) is independently 50 g / cm 2 -80g / cm 2 .
[0023] Furthermore, the hydrophilic material includes at least one of polyvinyl alcohol, polyaniline and perfluorosulfonic acid resin.
[0024] The second aspect of the present application provides a method for preparing the membrane electrode, comprising the following steps:
[0025] Prepare a hydrophilic microporous layer slurry, mix the hydrophilic material and the first conductive solid material, add n-propanol, and disperse them uniformly to obtain the hydrophilic microporous layer slurry;
[0026] The hydrophilic microporous layer slurry is uniformly coated on the surface of the first hydrophobic microporous layer, and the hydrophilic microporous layer is formed after drying to obtain an anode gas diffusion layer with a hydrophilic microporous layer;
[0027] The membrane electrode is then obtained by pressing together the anode gas diffusion layer, the anode catalyst layer, the proton exchange membrane, the cathode catalyst layer and the cathode gas diffusion layer in this order.
[0028] A third aspect of the present invention provides a proton exchange membrane fuel cell, comprising the membrane electrode.
[0029] Compared with the prior art, the present invention has at least the following beneficial effects:
[0030] The membrane electrode provided by the present invention is provided with a hydrophilic microporous layer in the anode gas diffusion layer, and the water in the anode catalyst layer is first absorbed and transferred through the hydrophilic microporous layer, and then transferred and discharged through the hydrophobic microporous layer, thereby ensuring that the water at the interface between the membrane electrode catalyst layer and the microporous layer is discharged in time, and at the same time, the water and gas are secondary distributed at the interface more evenly, thereby avoiding the occurrence of hydrogen deficiency reversal on the anode side and improving the life of the membrane electrode.
[0031] The proton exchange membrane fuel cell provided by the present invention uses a membrane electrode with better performance, thereby improving the performance of the proton exchange membrane fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 A schematic diagram of the structure of a membrane electrode provided by the present invention;
[0034] Figure 2 Voltage variation trend diagram of Example 1 and Comparative Example 1 under different currents provided for Test Example 2;
[0035] Figure 3 The voltage variation trend diagram under different currents of Example 2 and Comparative Example 2 provided for Test Example 2.
[0036] Icon: 10-anode gas diffusion layer; 12-first substrate layer; 14-first hydrophobic microporous layer; 16-hydrophilic microporous layer; 20-anode catalyst layer; 30-proton exchange membrane; 40-cathode catalyst layer; 50-cathode gas diffusion layer; 52-second hydrophobic microporous layer; 54-second substrate layer. DETAILED DESCRIPTION
[0037] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but those skilled in the art will understand that the following embodiments and examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0038] The first aspect of the present invention provides a membrane electrode, comprising an anode gas diffusion layer, an anode catalyst layer, a proton exchange membrane, a cathode catalyst layer and a cathode gas diffusion layer stacked in sequence;
[0039] The anode gas diffusion layer includes a hydrophilic microporous layer.
[0040] The membrane electrode provided by the present invention is provided with a hydrophilic microporous layer in the anode gas diffusion layer, and the water vapor generated by the anode catalyst layer is first absorbed and transferred through the hydrophilic microporous layer, and then transferred and discharged through the hydrophobic microporous layer, so that the water and gas on the anode side are evenly distributed, flooding is avoided, the gas mass transfer process on the anode side is improved, and the normal operation of the membrane electrode is guaranteed.
[0041] The schematic diagram of the membrane electrode structure is as follows Figure 1 As shown, it specifically includes an anode gas diffusion layer 10, an anode catalyst layer 20, a proton exchange membrane 30, a cathode catalyst layer 40 and a cathode gas diffusion layer 50 which are stacked in sequence;
[0042] The anode gas diffusion layer 10 includes a hydrophilic microporous layer 16 .
[0043] In some embodiments of the present invention, the anode gas diffusion layer 10 includes a hydrophilic microporous layer 16 , a first hydrophobic microporous layer 14 , and a first substrate layer 12 which are stacked in sequence.
[0044] The cathode gas diffusion layer 50 includes a second base layer 54 and a second hydrophobic microporous layer 52 which are stacked in sequence.
[0045] In some embodiments of the present invention, the hydrophilic microporous layer 16 is disposed on a side close to the anode catalyst layer 20 , and the first substrate layer 12 is disposed on a side away from the anode catalyst layer 20 .
[0046] In some embodiments of the present invention, the second substrate layer 54 is disposed on a side away from the cathode catalyst layer 40 , and the second hydrophobic microporous layer 52 is disposed on a side close to the cathode catalyst layer 40 .
[0047] In some embodiments of the present invention, the hydrophilic microporous layer 16 has a thickness of 1 μm-10 μm.
[0048] When the thickness of the hydrophilic microporous layer is less than 1 μm, water cannot be evenly distributed, and the effect of gas secondary distribution cannot be achieved. When the thickness is greater than 10 μm, the resistance to gas mass transfer is increased, and the path for water to conduct to the first hydrophobic microporous layer 14 is increased, increasing the risk of flooding.
[0049] In some embodiments of the present invention, the thickness of the hydrophilic microporous layer is typically, but not limited to, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.
[0050] Preferably, the material of the hydrophilic microporous layer includes 3wt.%-30wt.% of hydrophilic material and the remainder of the first conductive solid material.
[0051] When the proportion of hydrophilic material is less than 3wt.%, the hydrophilic effect cannot be prominent and the effect of uniform water distribution cannot be formed; when the proportion of hydrophilic material is higher than 30wt.%, the hydrophilic component is too high and flooding is prone to occur. In some embodiments of the present invention, the proportion of hydrophilic material is typically but not limited to 3wt.%, 5wt.%, 7wt.%, 9wt.%, 11wt.%, 13wt.%, 15wt.%, 17wt.%, 19wt.%, 20wt.%, 21wt.%, 23wt.%, 25wt.%, 27wt.%, 29wt.% or 30wt.%.
[0052] Preferably, the first hydrophobic microporous layer and the second hydrophobic microporous layer are both made of a hydrophobic material and a second conductive solid material.
[0053] The present invention is not limited to a specific type of hydrophobic material, as long as it is a material that can be used in a gas diffusion layer and has a hydrophobic function.
[0054] Furthermore, the first conductive solid material and the second conductive solid material independently include at least one of carbon powder, carbon fiber, metal powder, conductive polymer material and polymer material with a conductive material coated on the outer layer.
[0055] Preferably, the first conductive solid material is carbon fiber.
[0056] Preferably, the aspect ratio of the carbon fiber is 10 to 500. For two-dimensional materials with a large aspect ratio, water is conducted along the outer wall of the fiber, and the pores between them can conduct gas, which can effectively and quickly transfer the water generated by the catalytic layer to the hydrophobic microporous layer, and then conduct it to the flow channel to achieve the purpose of drainage.
[0057] In some embodiments of the present invention, the aspect ratio of the carbon fibers is typically, but not limited to, 10, 50, 100, 150, 200, 300, 400, or 500.
[0058] Furthermore, the first substrate layer and the second substrate layer independently include carbon paper, carbon cloth, carbon felt or non-woven fabric.
[0059] Furthermore, the water contact angles of the first hydrophobic microporous layer and the second hydrophobic microporous layer are independently 120°-150°. The hydrophobic microporous layer within this water contact angle range has a good hydrophobic effect.
[0060] Preferably, the surface density range of (the first hydrophobic microporous layer + the first substrate layer) and (the second hydrophobic microporous layer + the second substrate layer) is independently 50 g / cm 2 -80g / cm 2 The hydrophobic microporous layer within this range has a uniform coating of hydrophobic material and better hydrophobic function, which can take into account both hydrophobic and mass transfer functions. (The first hydrophobic microporous layer + the first substrate layer) and (the second hydrophobic microporous layer + the second substrate layer) refer to the surface density obtained by testing the substrate layer and the hydrophobic microporous layer as a whole.
[0061] Furthermore, the hydrophilic material includes at least one of polyvinyl alcohol, polyaniline and perfluorosulfonic acid resin.
[0062] The second aspect of the present application provides a method for preparing the membrane electrode, comprising the following steps:
[0063] A hydrophilic microporous layer slurry is prepared, and after coating and drying, an anode gas diffusion layer with a hydrophilic microporous layer is obtained;
[0064] The membrane electrode is then obtained by pressing together the anode gas diffusion layer, the anode catalyst layer, the proton exchange membrane, the cathode catalyst layer and the cathode gas diffusion layer in this order.
[0065] A third aspect of the present invention provides a proton exchange membrane fuel cell, comprising the membrane electrode.
[0066] The proton exchange membrane fuel cell provided by the present invention uses a membrane electrode with better performance, thereby improving the performance of the proton exchange membrane fuel cell.
[0067] The present invention is further described below by specific examples and comparative examples, but it should be understood that these examples are only used for more detailed description and should not be understood as limiting the present invention in any form. The raw materials used in the examples and comparative examples of the present invention, if no specific conditions are specified, are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0068] Example 1
[0069] This embodiment provides a membrane electrode, and the preparation method is as follows:
[0070] 1. Prepare hydrophilic microporous layer slurry: Take 2 g of vapor grown carbon fiber (VGCF, Showa Denko), 0.18 g of perfluorosulfonic acid resin, and 20 g of n-propanol, and disperse them evenly to obtain hydrophilic microporous layer slurry.
[0071] 2. Take a gas diffusion layer (055, Toray), which has a hydrophobic microporous layer with a surface density of 56g / cm 2 , water contact angle 125°. The hydrophilic microporous layer slurry of step 1 was coated on the hydrophobic microporous layer with a thickness of 10 μm, and dried at 80° C. for 30 min to obtain an anode gas diffusion layer.
[0072] 3. Pressing the anode gas diffusion layer, the anode catalyst layer, the proton exchange membrane, the cathode catalyst layer and the cathode gas diffusion layer together to obtain a membrane electrode.
[0073] Example 2
[0074] This embodiment provides a membrane electrode, and the preparation method is as follows:
[0075] 1. Prepare hydrophilic microporous layer slurry: Take 2g of Denka carbon powder, 0.12g of perfluorosulfonic acid resin, and 20g of n-propanol, and disperse them evenly to obtain hydrophilic microporous layer slurry.
[0076] 2. Take a gas diffusion layer (GDS3260, Avcarb), which has a hydrophobic microporous layer with a surface density of 80g / cm 2 , water contact angle 140°. The hydrophilic microporous layer slurry of step 1 was coated on the hydrophobic microporous layer with a thickness of 10 μm, and dried at 80° C. for 30 min to obtain an anode gas diffusion layer.
[0077] 3. Same as Example 1.
[0078] Example 3
[0079] This embodiment provides a membrane electrode, and the preparation method is as follows:
[0080] 1. Prepare hydrophilic microporous layer slurry: Take 2 g of vapor grown carbon fiber (VGCF, Showa Denko), 0.18 g of perfluorosulfonic acid resin, and 20 g of n-propanol, and disperse them evenly to obtain hydrophilic microporous layer slurry.
[0081] 2. Take a gas diffusion layer (GDS3260, Avcarb), which has a hydrophobic microporous layer with a surface density of 80g / cm 2 , water contact angle 140°. The hydrophilic microporous layer slurry of step 1 was coated on the hydrophobic microporous layer with a thickness of 10 μm, and dried at 80° C. for 30 min to obtain an anode gas diffusion layer.
[0082] 3. Same as Example 1.
[0083] Example 4
[0084] This embodiment provides a membrane electrode, and the preparation method is as follows:
[0085] 1. Prepare hydrophilic microporous layer slurry: Take 2g of Denka carbon powder, 0.12g of perfluorosulfonic acid resin, and 20g of n-propanol, and disperse them evenly to obtain hydrophilic microporous layer slurry.
[0086] 2. Take a gas diffusion layer (055, Toray), which has a hydrophobic microporous layer with a surface density of 56g / cm 2 , water contact angle 125°. The hydrophilic microporous layer slurry of step 1 was coated on the hydrophobic microporous layer with a thickness of 10 μm, and dried at 80° C. for 30 min to obtain an anode gas diffusion layer.
[0087] 3. Same as Example 1.
[0088] Example 5
[0089] This embodiment provides a membrane electrode. The difference from Embodiment 1 is that the mass of the perfluorosulfonic acid resin is 1 g, and the other raw materials and methods are the same as those in Embodiment 1, which will not be described again.
[0090] Example 6
[0091] This embodiment provides a membrane electrode. The difference from the embodiment 1 is that the thickness of the hydrophilic microporous layer is 0.5 μm. The other raw materials and methods are the same as those in the embodiment 1 and will not be described again.
[0092] Example 7
[0093] This embodiment provides a membrane electrode. The difference from the embodiment 1 is that the thickness of the hydrophilic microporous layer is 15 μm. The other raw materials and methods are the same as those in the embodiment 1 and will not be described again.
[0094] Example 8
[0095] This embodiment provides a membrane electrode. The difference from Embodiment 1 is that the aspect ratio of the vapor-grown carbon fiber is 5. The remaining raw materials and methods are the same as those in Embodiment 1 and will not be described again.
[0096] Comparative Example 1
[0097] This comparative example provides a membrane electrode, which is different from Example 1 in that a hydrophilic microporous layer is not provided, and the remaining raw materials and steps are the same as those in Example 1, which will not be repeated here.
[0098] Comparative Example 2
[0099] This comparative example provides a membrane electrode, which is different from Example 2 in that a hydrophilic microporous layer is not provided, and the remaining raw materials and steps are the same as those of Example 2, which will not be repeated here.
[0100] Test Example 1
[0101] The membrane electrode obtained from Examples 1-8 and Comparative Examples 1-2 was subjected to a single cell performance test, and the test process was as follows: the test conditions were cell temperature 80°C, anode / cathode back pressure 270 / 260 kPa, anode / cathode stoichiometric ratio 2.0 / 2.3, and anode / cathode humidity 50% / 50%.
[0102] Take 2.0A / cm 2 The voltage is lowered and the obtained data is shown in Table 1 below.
[0103] Table 1
[0104]
[0105]
[0106] As can be seen from Table 1, the performance of Example 1 is improved compared with Comparative Example 1, and that of Example 3 is improved compared with Comparative Example 2, indicating that the use of carbon fibers with a certain aspect ratio and a hydrophilic microporous layer with a certain proportion of hydrophilic materials added to different gas diffusion layers containing hydrophobic microporous layers can significantly improve the performance.
[0107] By comparing Example 1 with Example 4, and Example 2 with Example 3, it can be seen that the hydrophilic microporous layer using carbon fibers has better performance than that using traditional ball carbon black. This is because the pores between the carbon fibers can significantly improve the mass transfer performance.
[0108] The performance of Example 5 is the lowest, which is due to excessive addition of hydrophilic agent, resulting in excessive water retention and water flooding.
[0109] The performance of Example 6 and Example 7 is improved to a certain extent, but the thickness of the microporous layer is either too thin to produce weak effects, or too thick to produce negative effects.
[0110] Example 8 uses low aspect ratio carbon fiber, and the performance is improved to a certain extent, but worse than Example 1. After the aspect ratio decreases, the pore size between the carbon fibers becomes smaller, and the mass transfer enhancement effect is weakened.
[0111] Test Example 2
[0112] The membrane electrode obtained from Example 1-2 and Comparative Example 1-2 was subjected to a single cell performance test, and the test process was as follows: the test conditions were cell temperature 80°C, anode / cathode back pressure 270 / 260 kPa, anode / cathode stoichiometric ratio 2.0 / 2.3, and anode / cathode humidity 50% / 50%.
[0113] Test the voltage under different current densities and plot the data of Example 1 and Comparative Example 1 to obtain Figure 2 , the data of Example 2 and Comparative Example 2 are plotted to obtain Figure 3 .
[0114] from Figure 2 and Figure 3 It can be seen that, by comparing Example 1 with Comparative Example 1, and by comparing Example 2 with Comparative Example 2, the addition of the hydrophilic microporous layer significantly improves the battery performance.
[0115] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A membrane electrode, characterized in that: It includes an anode gas diffusion layer, an anode catalyst layer, a proton exchange membrane, a cathode catalyst layer and a cathode gas diffusion layer which are stacked in sequence; The anode gas diffusion layer includes a hydrophilic microporous layer.
2. The membrane electrode according to claim 1, characterized in that: The anode gas diffusion layer comprises a hydrophilic microporous layer, a first hydrophobic microporous layer and a first substrate layer which are stacked in sequence; the cathode gas diffusion layer comprises a second hydrophobic microporous layer and a second substrate layer which are stacked in sequence.
3. The membrane electrode according to claim 2, characterized in that: The first substrate layer is arranged on a side away from the anode catalyst layer, and the hydrophilic microporous layer is arranged on a side close to the anode catalyst layer.
4. The membrane electrode according to claim 2, characterized in that: The thickness of the hydrophilic microporous layer is 1 μm-10 μm; Preferably, the material of the hydrophilic microporous layer includes 3wt.%-30wt.% of hydrophilic material and the remainder of the first conductive solid material; Preferably, the first hydrophobic microporous layer and the second hydrophobic microporous layer are both made of a hydrophobic material and a second conductive solid material.
5. The membrane electrode according to claim 4, characterized in that: The first conductive solid material and the second conductive solid material independently include at least one of carbon powder, carbon fiber, metal powder, conductive polymer material and polymer material with a conductive material coated on the outer layer; Preferably, the first conductive solid material is carbon fiber; Preferably, the aspect ratio of the carbon fiber is 10-500.
6. The membrane electrode according to claim 2, characterized in that: The first substrate layer and the second substrate layer independently include one of carbon paper, carbon cloth, carbon felt or non-woven fabric.
7. The membrane electrode according to claim 2, characterized in that: The water contact angles of the first hydrophobic microporous layer and the second hydrophobic microporous layer are independently 120°-150°; Preferably, the surface density of the (first substrate layer + first hydrophobic microporous layer) and the (second substrate layer + second hydrophobic microporous layer) is independently 50 g / cm 2 -80g / cm 2 .
8. The membrane electrode according to claim 4, characterized in that: The hydrophilic material includes at least one of polyvinyl alcohol, polyaniline and perfluorosulfonic acid resin.
9. A method for preparing a membrane electrode according to any one of claims 4 to 8, characterized in that: The following steps are involved: Prepare a hydrophilic microporous layer slurry, mix the hydrophilic material and the first conductive solid material, add n-propanol, and disperse them uniformly to obtain the hydrophilic microporous layer slurry; The hydrophilic microporous layer slurry is uniformly coated on the surface of the first hydrophobic microporous layer, and the hydrophilic microporous layer is formed after drying to obtain an anode gas diffusion layer with a hydrophilic microporous layer; The membrane electrode is then obtained by pressing together the anode gas diffusion layer, the anode catalyst layer, the proton exchange membrane, the cathode catalyst layer and the cathode gas diffusion layer in this order.
10. A proton exchange membrane fuel cell, characterized in that: The invention comprises the membrane electrode according to any one of claims 1 to 8.
Citation Information
Cited By
Gas diffusion layer and preparation method and application thereof
CN121260817A
Integrated fuel cell membrane electrode and preparation method thereof
CN121307109A